Grounded ridge detection and characterization along the Alaska Arctic coastline using ICESat-2 surface height retrievals - K. A. Lange; A. C. Bradley; K. Duncan; S. L. Farrell (The Cryosphere)
Grounded sea ice ridges are important morphological features that stabilize shorefast ice along Arctic coastlines. Investigating first the development of shorefast ice around Utqiaġvik, Alaska, we employ high-resolution altimetry data from NASA's ICESat-2 satellite to identify grounded ridges and to track the development of shorefast ice over the winter season. We apply the University of Maryland Ridge Detection Algorithm (Duncan and Farrell, 2022) using ICESat-2 ATL03 elevation data to identify and calculate ridge sail heights and estimate ridge depths using empirical relationships based on first-year ice ridge geometries surveyed in the Beaufort, Chukchi, and Bering seas. The estimated ridge depths are then compared with 15 arcsec resolution bathymetric data from the General Bathymetric Chart of the Oceans (GEBCO) to detect likely grounded ridges. This approach for identifying and characterizing grounded ridges in shorefast ice is then applied across 1500 km of the Alaska Arctic coastline in the 2021–2022 winter to characterize 2442 grounded ridge depth, height, grounding width, and distance from shore. Using a range of depth estimates, each ridge is classified as high, medium, or low confidence. We find that grounded ridges along the Chukchi Sea coast tend to be located closer to shore, wider, and ground at shallower depths than those along the Beaufort coast. High-confidence ridge detections tend to be taller, shallower, and closer to shore than lower-confidence retrievals along both coastlines. Only 12 % of all ridge detections in the Chukchi Sea and 28 % in the Beaufort Sea are located within the traditional “stamukhi” zone (≥10 m). Finally, seasonal signatures can be identified in the data despite the low-temporal-resolution product, suggesting that subsequent events not only increase the height of nearshore ridges but also form additional ridges at greater bathymetric depths throughout the season. With further application of the methods demonstrated here, we can begin to map patterns in shorefast ice stability and seasonality and improve our understanding of nearshore ice dynamics across Arctic coastal regions in a changing climate.